2019
DOI: 10.3390/ijms20051239
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Curcumin in the Modulation of Ageing

Abstract: It is believed that postponing ageing is more effective and less expensive than the treatment of particular age-related diseases. Compounds which could delay symptoms of ageing, especially natural products present in a daily diet, are intensively studied. One of them is curcumin. It causes the elongation of the lifespan of model organisms, alleviates ageing symptoms and postpones the progression of age-related diseases in which cellular senescence is directly involved. It has been demonstrated that the elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 185 publications
(234 reference statements)
1
71
0
1
Order By: Relevance
“…It has been demonstrated that up to 8 g/ day is a pharmacologically safe dosage range for Cur [66]. The highest intake of Cur to date has been reported in India (100 mg/day) [67]. While the dosage used in the present study is somewhat higher than the dose normally consumed by humans, it still remains less than toxic dose.…”
Section: Discussionmentioning
confidence: 61%
“…It has been demonstrated that up to 8 g/ day is a pharmacologically safe dosage range for Cur [66]. The highest intake of Cur to date has been reported in India (100 mg/day) [67]. While the dosage used in the present study is somewhat higher than the dose normally consumed by humans, it still remains less than toxic dose.…”
Section: Discussionmentioning
confidence: 61%
“…Spermidine and butyrate are known to reduce inflammation by targeting NF- κ B, G-protein–coupled receptors, autophagy, or inhibiting HDAC class1 [ 29 , 30 ]. In addition, the expression of many SASP components such as IL8 or IL6 are regulated by the activity of the transcription factor NF- κ B, responsible for the development of inflammation [ 31 ]. In our study, we could not observe any significant anti-inflammatory effects of spermidine and butyrate.…”
Section: Discussionmentioning
confidence: 99%
“…159 This has made it a popular compound in anti-aging research. 160 Curcumin treatment in vitro protects human adipose-derived MSCs (aMSCs) from death when exposed to H 2 O 2 and enhances osteogenic potential through attenuation of oxidative stress and Wnt/β-catenin signaling inhibition. 161 However, this effect may be cell type-dependent.…”
Section: Curcumin and Nogginmentioning
confidence: 99%